The role of responsibility accounting in performance evaluation: A case study of the general company for food products (Amin factory) (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to demonstrate the importance of applying responsibility accounting in economic units and its role in evaluating the performance of responsibility centers by shedding light on responsibility centers and ensuring commitment to implementing the policies and objectives of the economic unit. The problem lies in the fact that the use of traditional methods of performance evaluation results from a lack of attention to administrative accounting aspects and a focus on applying the responsibility accounting system through evaluating the performance of cost centers. Due to their reliance on traditional methods and the lack of sufficient information, this has led to a weakness in performance evaluation according to modern methods. In order to achieve the research objectives and verify the validity of its hypotheses, the responsibility accounting system was applied, and the industrial sector was chosen as the research community and the General Company for Food Products, represented by the Amin Factory, as the research sample. The research concluded with a set of conclusions and recommendations, the most important of which was that the research found that there is weakness and shortcomings in the accounting reports and information provided by the factory, and the neglect of the aspect of preparing monthly, quarterly and annual reports, including the preparation of the annual budget plan to identify deviations and determine their causes to work on finding solutions that help in raising the effectiveness and efficiency of operations within the factory. The study recommends that responsibility centers should be defined accurately and clearly, with the responsibilities and activities associated with them and how to allocate costs to each center being clarified. The factory should work on improving production and administrative operations in the various responsibility centers in order to improve the overall performance of the factory. The accounting and evaluation system should be developed to be more comprehensive and effective, including the definition of clear and measurable performance standards for evaluating the performance of responsibility centers.